Jamak Qillah dan Katsroh dalam Sorotan Linguistik: Antara Aturan Morfologi dan Realitas Konteks - Akmaluddin Akmaluddin (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2025)
This study revisits the classification system of broken plurals (jamak taksir) in Arabic, focusing on the categories of jamak qillah (few) and jamak katsrah (many), through a modern linguistic lens encompassing semantic, pragmatic, and corpus-based approaches. Traditional morphological classifications often fail to reflect actual meanings in context, particularly in Qur’anic discourse. Using a qualitative descriptive method combined with corpus linguistics technology, this research explores the dynamics of meaning and function of plural forms in the Qur'an. The findings reveal that jamak qillah and jamak katsrah forms do not consistently denote quantity in a literal sense, but are often selected for rhetorical, thematic, or communicative purposes. Consequently, the teaching of Arabic morphology and exegetical studies should adopt a more contextual and data-driven approach